Standarisasi Mahar Pernikahan Dalam Perspektif Imam Abu Hanifah - Burhan, Ali; Bahrosi, Ahmad (Universitas Bondowoso, 2023)
As social creatures, humans certainly really need other humans to carry out their lives and for the lives of their generations. To continue life for future generations, humans must marry. Marriage or marriage will not take place without the presence of the opposite sex. It is sunnatullah that the nature of every human being is created in pairs. male and female for humans and male and female for animals. day and night for the time cycle. Marriage is one of the most civilized ways for humans to fulfill their biological needs. This method is what differentiates humans from animals. A marriage or marriage will take place after going through several stages, such as starting with a sermon or engagement and then carrying out a marriage contract at a later date. Of course, this cannot be separated from the dowry that must be given to his future wife. Talking about the issue of dowry, the Ulama' of the school of thought have views that are sometimes the same and sometimes different, one of which is Imam Abu Hanifah. The Ulama' of the Imam Abu Hanifah school of thought is of the opinion that the dowry stated in the marriage contract cannot be less than ten dirhams. From this case, researchers are interested in conducting research on the standardization of marriage dowries. The problem to be answered is the standardization of the maximum dowry and the standardization of the minimum dowry according to Imam Abu Hanifah's perspective. To answer the problems in this research, the author first collected data, both primary and secondary data. After the data was collected, the writer analyzed the data using the theory of dowry, then the researcher concluded on the standardization of dowry from Imam Abu Hanifah's perspective. In this research, researchers obtained several findings or answers. The first is the maximum standard of dowry from the perspective of Imam Abu Hanifah and the imams of other schools of thought. secondly, the minimum dowry standard from Imam Abu Hanifah's perspective.